Improving volleyball competence: E-module-based volleyball learning media innovation - Kasih, Indra; Faridah, Eva; Widianingsih, Onyas; Sinulingga, Albadi; Amirzan (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
The urgent need for the creation of cutting-edge learning media in the context of volleyball learning served as the driving force behind this study. The main objective was to develop and validate the E-Module as an innovative learning tool specifically focused on skill development in volleyball. The research method applied was the development method with the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). Data collection was done through questionnaires and documentation, while data analysis used quantitative descriptive techniques. The results showed that E-Module as an innovative learning tool in volleyball can be developed successfully. This finding highlighted the important role of experts in the development of e-modules and opened up new insights into the potential of technology in supporting the learning of sport practices, especially in the context of volleyball. While the results of this study showed a positive impact, there are limitations in the context and sample of the study. Therefore, further research is needed to explore the impact of student motivation on the use of the E-Module in volleyball learning as well as generalise these findings to other sport learning contexts. This E-Module can not only be a reference for further research in the field of sports learning media development, especially volleyball, but also be recognised as an excellent product of E-Module-Based Volleyball Learning. Thus, this research contributes not only to academic knowledge but also to the practice of sports learning, especially volleyball.